2013
DOI: 10.1074/jbc.m113.529347
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nuclear Factor κB (NF-κB) in the Nucleus of Cardiomyocytes by G Protein-coupled Receptor Kinase 5 (GRK5)

Abstract: Background: NF-B activation and GRK5 up-regulation have been shown to be associated with heart disease. Results: GRK5 induces NF-B signaling pathway both in cardiomyocytes and in mouse hearts. Conclusion: GRK5 triggers the binding of NF-B (p50/p65) to DNA in the nucleus and promotes gene transcription including hypertrophic gene. Significance: GRK5 up-regulation may lead to a significant increase in expression and activation of NF-B seen in heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Activation of NF〉 led to binding of p50 and p65 to the GRK5 promoter and subsequent increase in GRK5 expression after hypertrophic stimuli (115). Conversely to the mechanism proposed in FIGURE 5A, overexpression of GRK5 increased levels of p50 and p65, and silencing of GRK5 led to decreased levels of p50 and p65 and loss of NF〉 DNA binding activity (114). A schematic of the latter mechanism is shown in FIGURE 5B.…”
Section: A Grk5 and Its Role In Pathological Cardiac Hypertrophy Andmentioning
confidence: 71%
See 1 more Smart Citation
“…Activation of NF〉 led to binding of p50 and p65 to the GRK5 promoter and subsequent increase in GRK5 expression after hypertrophic stimuli (115). Conversely to the mechanism proposed in FIGURE 5A, overexpression of GRK5 increased levels of p50 and p65, and silencing of GRK5 led to decreased levels of p50 and p65 and loss of NF〉 DNA binding activity (114). A schematic of the latter mechanism is shown in FIGURE 5B.…”
Section: A Grk5 and Its Role In Pathological Cardiac Hypertrophy Andmentioning
confidence: 71%
“…Further studies have also confirmed GRK5 as a mediator of NF〉 signaling in mammals, with potential implications in cardiac hypertrophy and other cardiovascular pathologies, although the mechanism of action is still not fully understood (114,170,232). NF〉 is a highly regulated dimeric transcription factor present as heterodimers (p50:p65) or homodimers (p50:p50 or p65:p65) (87).…”
Section: A Grk5 and Its Role In Pathological Cardiac Hypertrophy Andmentioning
confidence: 99%
“…However, it is also possible that decreased NF-B activation could be a result of the previously demonstrated role of GRK5 in NF-B signaling (11,38). GRK5 has been shown to regulate NF-B signaling positively (macrophages) (10) or negatively (endothelial cells) (38) and to modulate inflammatory response depending on the cell type involved (39). We have shown that in endotoxemia (20) and polymicrobial sepsis (19), GRK5 mediates cytokine production and GRK5 KO mice exhibit an attenuated inflammatory response.…”
Section: Discussionmentioning
confidence: 91%
“…Wherein mice generated by the Lefkowitz group (Wu et al, 2012) found that endothelial GRK5 stabilized IκBα similar to earlier studies by Sorriento et al (Daniela Sorriento et al, 2008), studies done in macrophages using a different GRK5 knock out mice did not show any role for GRK5 in IκBα phosphorylation or p65 translocation. More recent studies using mice from the Lefkowitz group, however, have shown that GRK5 positively regulates the NFκB pathway in cardiomyocytes (Islam, Bae, Gao, & Koch, 2013). It is unclear the exact reasoning behind these discrepancies in GRK5 behavior but it has also been shown that GRK5 itself can be regulated by the NFκB pathway, generating a potential positive feedback loop between GRK5 and NFκB (Islam & Koch, 2012).…”
Section: Grks In Inflammatory Signaling and Diseasementioning
confidence: 99%